(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
In order to meet consumer and legislation requirements, big investments on key technology strategies have been made to ensure fuel consumption is reduced. Recent technologies for gasoline engines are lean combustion technologies (including direct injection and homogenous charged compression ignition), optimizing intake and exhaust valve timing with valve lift and also cylinder deactivation system (CDA) have been practised to improve the engine efficiency. The purpose of this study is to investigate the engine behavior when running at different cylinder deactivation (CDA) strategies. One-dimensional engine model software called GT-Power is used to predict the engine performances. Five strategies were considered namely normal mode, spark plug off mode, cylinder deactivation mode, intake normal with exhaust off mode, and intake off with exhaust normal mode. Â Engine performance outputs of each strategy are predicted and compared at BMEP of 3 bars with engine speed of 2500 rpm. Also, the effect of CDA strategies on in-cylinder pressure and pumping loss are performed. The study shows that all of these cylinder deactivation strategies are capable of reducing the pumping loss (PMEP) and fuel consumption, thus increasing the thermal efficiency of the engine. The results suggest that the most beneficial strategy for activating CDA is for the case whereby both the intake and exhaust valves are kept closed. This CDA mode capable of increasing brake thermal efficiency up to 22% at entire engine speeds operation. This strategy successfully reduced the BSFC. It was found that most of these cylinder deactivation strategies improve the engine performance during part load engine condition